Analisis Kualitas Sensori Kue Putu Ayu dengan Penambahan Ekstrak Buah Naga Merah - Kurnia, Rahmi (YASIN, 2025)
This study aims to analyze the sensory quality of putu ayu cake with the addition of red dragon fruit extract at concentrations of 20%, 30%, and 40% as an effort to innovate traditional food products using natural ingredients—a practice that remains relatively uncommon. This research is a true experimental study using a Completely Randomized Design (CRD) with three replications, involving four treatments: control (X0) and three extract variations (X1, X2, X3). The assessment was conducted by five semi-trained panelists from the Culinary Arts faculty using organoleptic test sheets to evaluate color, aroma, and taste. Data were analyzed using quantitative descriptive statistics, followed by ANOVA and Duncan’s post hoc test. The results show that the addition of 40% red dragon fruit extract (X3) had the most significant effect on color, aroma, and the distinctive taste of dragon fruit, but did not significantly affect the cake’s sweetness. The control treatment (X0) recorded the highest score for sweetness (3.67), while X3 received the highest scores for aroma (2.53) and dragon fruit flavor (2.73). These findings indicate that red dragon fruit extract can enhance the visual appeal and distinctive taste profile of putu ayu without altering its sweetness, thus offering potential for enriching traditional food innovations with functional natural ingredients.